AoA and AoI in Modern Industrial Control - Sadikhov, Suleyman; Tärneberg, William; Fitzgerald, Emma ; 0000-0002-0836-4808; Peng, Haorui ; 0000-0001-5520-4674; Nyberg, Christian (2025 IEEE Wireless Communications and Networking Conference (WCNC), 2025)
Conventional Quality of Service(QoS) measurements are incapable to meet the demand for analysing communication performance on timeliness of information in Industrial Control Networks with many connected subsystems. The Age of Information (AoI) and the Age of Actuation (AoA) give a promise to be a solution. Many recent research articles cover theoretical aspects and analyse performance characteristics of communication systems in terms of AoI, but practical realisation in industry has not been achieved yet. As a new companion metric to AoI, AoA is evaluated in a real test-bed for the first time in this paper. All analysis is based on measurement in an Edge-Control System implemented as our test-bed. To validate the usefulness of these metrics in the system performance tests on edge-cloud integration, the test-bed separated to field network and edge-to-field network scenarios, where the edge server is located in a 5G base-station. This article also describes how such measurements can be carried out. Practical issues such as time synchronizations between connected devices and how to calculate AoI and AoA based on measurements are handled.
Keywords: Age of Information; Age of Actuation; Edge-Control; PTP synchronization